Interventions for bullous pemphigoid. - Khumalo, N; Kirtschig, G; Middleton, P; Hollis, S; Wojnarowska, F; Murrell, D (2003)
BACKGROUND: Bullous pemphigoid is the most common autoimmune bullous disease in the West. Oral steroids are considered the standard treatment. OBJECTIVES: To assess the effects of treatments for bullous pemphigoid. SEARCH STRATEGY: We searched the Skin Group Specialised Register, the Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE to March 2003 and bibliographies from identified studies. SELECTION CRITERIA: Randomised controlled trials of treatments for patients with immunofluorescence confirmed bullous pemphigoid. DATA COLLECTION AND ANALYSIS: Two reviewers evaluated the studies in terms of the inclusion criteria, five extracted data independently; disagreements were resolved by discussion. Statistical pooling of the data was inappropriate because of heterogeneity of treatments. MAIN RESULTS: We found seven randomised controlled trials with a total of 634 patients. All studies involved different comparisons, none included a placebo group. Different doses, different formulations of corticosteroids and the addition of azathioprine failed to show significant differences in measures of disease control. However, patients who took azathioprine were able to almost halve the amount of prednisone required for disease control. Plasma exchange plus prednisone achieved significantly better disease control than prednisone alone; this favourable effect was not apparent in another study. The latter study also compared plasma exchange or azathioprine plus prednisone, but failed to show significant differences for disease control or mortality, although total adverse events at six months almost reached statistical significance in favour of plasma exchange plus prednisone. Comparing tetracycline plus nicotinamide with prednisolone, no significant difference for disease response was shown. A very potent topical corticosteroid was compared to oral prednisone in patients with moderate and extensive disease. In patients with extensive disease, the topical steroid group showed significantly better survival and disease control, and less severe complications, while no significant differences for these outcomes were seen in patients with moderate disease. Most of the reported deaths were in patients taking high doses of oral corticosteroids. REVIEWER'S CONCLUSIONS: Very potent topical steroids are effective and safe treatments for bullous pemphigoid; their use in extensive disease may be limited by side effects and practical factors. Starting doses of prednisolone greater than 0.75 mg/kg/day do not seem to give additional benefit, lower doses may be adequate for disease control; this could reduce the incidence and severity of adverse reactions. The effectiveness of the addition of plasma exchange or azathioprine to corticosteroids has not been established. Combination treatment with tetracycline and nicotinamide may be useful; this needs further validation.